EXPLORING THE POTENTIAL OF SOCIAL MEDIA AS A HEALTH COMMUNICATION PLATFORM FOR FILICIDE PREVENTION IN INDONESIA: English - Asmawati, Mega Nur (PT. Jurnal Center Indonesia Publisher, 2025)
This study explores the potential of social media as a health communication platform for preventing filicide in Indonesia, focusing on disseminating information, reducing stigma, and engaging audiences. The study adopts an exploratory approach based on secondary data, including the analysis of scientific literature, reports from the Indonesian Child Protection Commission (KPAI) and UNICEF, and global campaigns such as #EndViolence. Research shows that social media can reach a broad audience, particularly the younger generation, through strategically designed educational content like infographics and videos. Empathy-driven campaigns utilizing real-life stories can also effectively reduce the stigma surrounding mental health, a primary cause of filicide. However, the study identifies challenges such as limited access in remote areas, potential misuse of platforms, and the sustainability of campaigns, which often pose obstacles. In Indonesia’s context, adapting global campaign models to local culture can enhance prevention outcomes. Collaboration among the government, non-profit organizations, and the community is key to ensuring long-term impact. By integrating technologies such as artificial intelligence and gamification, and implementing data-driven approaches, social media can become a powerful tool to drive behavioral change and raise public awareness about filicide prevention.